Resistance training and cardiovascular health: epigenetic regulation - Silva, João Gabriel; Rodrigues, Luis Felipe; Torres, Thyerre; Improta-Caria, Alex Cleber; Oliveira, Edilamar Menezes; Fernandes, Tiago (Frontiers in Physiology, 2026)
Resistance training plays a crucial role in cardiovascular health by promoting epigenetic adaptations that beneficially modulate gene expression. These modifications include DNA methylation, histone alterations, and regulation by non-coding RNAs, which directly affect cardiac muscle and the vascular system. Such epigenetic changes lead to improved cardiac function, reduced inflammation, optimized metabolism, and protection against cardiovascular diseases. Resistance training induces the release of signaling molecules that mediate favorable systemic adaptations. Studies demonstrate that resistance training, especially when combined with aerobic training, improves cardiovascular risk factors such as blood pressure and lipid profile. Epigenetic regulation is fundamental to the plasticity of the cardiovascular system and the reversibility of exercise-induced adaptations. Although extreme exercise may pose risks, regular and moderate resistance training is safe and effective in the prevention and management of cardiovascular diseases through these molecular mechanisms. Further investigation into these epigenetic modifications may unveil novel exercise-based therapeutic strategies to enhance cardiovascular health.